Der Arkadenhof der Universität Wien und die Tradition der Gelehrtenmemoria in Europa Wiener Jahrbuch für Kunstgeschichte, Band LXIII/LXIV - Schemper-Sparholz, Ingeborg; Engel, Martin; Mayr, Andrea; Rüdiger, Julia (2018)
Originating from the monumental ensemble of the arcade court of Vienna University, this thematic issue is dedicated to the traditon of academic memorials in a european-wide comparison. The first part of the volume focusses on the monuments of the Vienna University in context of development history and changing cultural and political framework conditions. The second part shows the european perspektive and focusses on the ancient and early modern era origins of the hall of honour, and the the different manifestation in chosen european countries until today. The issue contributes with its diverse methodical articles in a significant way to a discursive discussion on traditon and currency of academic memorials.